MENGENAL PENGOBATAN ALA RASULULLAH SAW SEBAGAI UPAYA PENYEMBUHAN PENYAKIT DI MASA PANDEMI COVID 19 - Rita Riyanti Kusumadewi; Indarwati Indarwati (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Background: The increase in the number of cases of Covid 19 causes a sense of worry and anxiety in the community of partner groups. Vaccines held by the government have not covered all circles. The results of a survey conducted in Kemiri, Kebakkramat found that there were several who had confirmed Covid 19. The solution for the anxiety and worries experienced by the community was a promotive model, namely by socializing the treatment of the Prophet SAW during the Covid 19 Pandemic to increase body immunity. Results: The targets in this study were the mothers of PKK Kebakkramat members. The output produced through this program is an increase in public knowledge about the medicine of the Prophet SAW. Methods: What is used is health education or socialization about the medicine of the Prophet SAW. which was attended by 19 people. The implementation is at the house of the local RT head. Results: This socialization received a positive and good response from the mothers of PKK Kemiri Kebakkramat members and there was a significant increase in knowledge of the mothers of PKK members about the treatment of the Prophet or Tibbun Nabawi. Conclusion: This outreach received a positive and good response from the target and there has been an increase in knowledge on the target about the treatment of the Prophet or Tibbun Nabawi. so that it can be applied in daily life to increase individual and family immunity during the COVID-19 pandemic.